Comparison of dental treatments performed under general anesthesia for healthy and disabled children - Nasser Kaviani; Maryam Ghafournia; Salim Mirzaali; Shirin Marzoughi; Reza Salari-Moghaddam (Wolters Kluwer Medknow Publications, 2021)
Background: This study aimed to assess and compare the type of dental procedures performed under general anesthesia for healthy and disabled children. Materials and Methods: This descriptive, cross-sectional study evaluated 361 dental records of children who received dental treatments under general anesthesia in the operating room of Torabinejad Research Center during 2011-2013. Patients with mental or physical disability were categorized as disabled. The age and gender of patients, number of treated teeth, duration of general anesthesia, type of tooth, and type of dental treatment such as extraction, pulp therapy, placement of stainless steel crowns, composite restoration, preventive resin restoration (PRR), fissure sealant treatment, and fluoride therapy were separately recorded for the healthy group and patients with disability. Data were analyzed using one-way ANOVA, and independent sample t-test at P < 0.05 level of significance. Results: Of 361 patients, 263 patients were healthy and 102 patients had disability. Of all disabled children, 48% had physical and 52% had mental disability. Among patients with physical disability, allergy (40%), followed by cardiovascular diseases (26%) were the most common. Mental retardation (54%) followed by cerebral palsy (10%) were the most common mental disabilities. Number of extracted teeth was significantly higher in disabled children (P = 0.006). Furthermore, disabled children received significantly lower PRR (P = 0.015), fissure sealant treatment (P = 0.003), fluoride therapy (P = 0.002), and pulp therapy (P < 0.001) compared with healthy children. Conclusion: Tooth extraction has a higher frequency in disabled children; while, attempts are made to preserve the teeth as much as possible in healthy children.